Returning straw and applying appropriate nitrogen fertilizer could increase acid-hydrolysable ammonium nitrogen and amino sugar nitrogen in the soil, thereby promoting effective panicle number and ultimately boosting rice yield - Linya Lu; Zhengli Song; Yang Hu; Liang Luo; Guiling Xu; Yuehua Feng; Muhammad Usama Latif; Somsana Phonenasay; Bingping Cui; Xiangjun Xu; Jianhua Huang; Yanni Wei (Plant and Soil, 2026)

ETV5 upregulates PD-L1 transcription to inhibit cytotoxic CD8+ T cell proliferation in colorectal cancer - Fei Kuang; Zhongwen Hu; Longtao Huangfu; Guiling Yan; Swati Dhiman; Wenzheng Chen; Ziyu Li (Science China Life Sciences, 2026)

Study on the pore structure evolution of granodiorite after cyclic thermal shock - Shutao Zhou; Qiang Sun; Guiling Wang; Xiting Long; Jianjun Hu; Tingxin Li (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

3-Phenoxybenzoic Acid Induces Neuronal Pentraxin 2 to Upregulate Complement Activity and Promotes Microglia-Mediated Neuronal Synaptic Damage - Guiling Hu; Kaidong Wang; Chenyang Wu; Qi Liu; Qianrong Zhang; Ai Qi; Min Huang (Journal of Molecular Neuroscience, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Toxic mechanisms of nanoplastics exposure at environmental concentrations on juvenile red swamp crayfish (Procambarus clarkii): From multiple perspectives - Long Wang; Qianqian Zhu; Meng Hu; Xinyi Zhou; Tianyu Guan; Nan Wu; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Environmental Pollution, 2024)

The spatial patterns and driving mechanisms of blue carbon ‘loss’ and ‘gain’ in a typical mangrove ecosystem: A case study of Beihai, Guangxi Province of China - Zhenxi Xie; Haonan Li; Yuan Yuan; Wei Hu; Gang Luo; Longtian Huang; Mo Chen; Weimei Wu; Guiling Yan; Xiang Sun (Science of The Total Environment, 2023)

Deep structure of the Rongcheng geothermal field, Xiongan New Area: Constraints from resistivity data and boreholes - Yunqi Zhu; Diquan Li; Yanfang Hu; Xian Zhang; Fu Li; Feng Ma; Guiling Wang (Geothermics, 2023)

G-CSF promotes the viability and angiogenesis of injured liver via direct effects on the liver cells - Zifeng Liu; Guiling Zhang; Jing Chen; Jingjing Tong; Hongmin Wang; Jing Chen; Dong Yang; Jinhua Hu (Molecular Biology Reports, 2022)
Background Presently, liver transplantation is the only treatment strategy for liver failure (LF). Although granulocyte-colony stimulating factor (G-CSF) exhibits protective functions in LF, it is not clear whether it directly affects the liver cells. Methods and Results We established an injured liver cell model and observed that G-CSF treatment promoted cell viability and enhanced Ki67 and VEGF-A expression. Thereafter, human umbilical vein endothelial cells (HUVECs) were cultured in a conditioned medium collected from the G-CSF-treated injured liver cells. HUVECs’ proliferation and tubule formation were promoted. Furthermore, in an injured liver mouse model, confirmed via haematoxylin–eosin staining, we evaluated serum alanine aminotransferase activity, Ki67 expression, and microvessel density (MVD). G-CSF treatment significantly relieved liver injury, upregulated Ki67 expression, and enhanced MVD in the injured mouse liver tissue. Additionally, AKT and ERK signal targets were explored, and it was demonstrated that the effects of G-CSF on injured liver cells were mediated through the AKT and ERK signalling pathways. Conclusions G-CSF promotes injured liver viability and angiogenesis by directly affecting injured liver cells via the AKT and ERK signalling pathways. These findings improve our understanding of the role of G-CSF in recovery from LF.

Molecular characteristics and pathogenicity of an equid alphaherpesvirus 1 strain isolated in China - Yue Hu; Qinrui Jia; Jianhua Liu; Wencheng Sun; Zilei Bao; Chuanzhong Che; Guiling Wu; Bin Fan; Jarhen; Duoliang Ran (Virus Genes, 2022)

LncRNA NEAT1 contributes to the acquisition of a tumor like-phenotype induced by PM 2.5 in lung bronchial epithelial cells via HIF-1α activation - Pan Jiang; Shengyu Hao; Liang Xie; Guiling Xiang; Weiping Hu; Qinhan Wu; Zilong Liu; Shanqun Li (Environmental Science and Pollution Research, 2021)

Impact of histaminergic H3 receptor antagonist on hypoglossal nucleus in chronic intermittent hypoxia conditions - Liang Xie; Qinhan Wu; Weiping Hu; Xu Wu; Guiling Xiang; Shengyu Hao; Han Guo; Shanqun Li (Psychopharmacology, 2021)

SIRT1 activation by pterostilbene attenuates the skeletal muscle oxidative stress injury and mitochondrial dysfunction induced by ischemia reperfusion injury - Yedong Cheng; Shouyin Di; Chongxi Fan; Liping Cai; Chao Gao; Peng Jiang; Wei Hu; Zhiqiang Ma; Shuai Jiang; Yushu Dong; Tian Li; Guiling Wu; et al. (Apoptosis, 2016)

Activation of endoplasmic reticulum stress is involved in the activity of icariin against human lung adenocarcinoma cells - Shouyin Di; Chongxi Fan; Yang Yang; Shuai Jiang; Miaomiao Liang; Guiling Wu; Bodong Wang; Zhenlong Xin; Wei Hu; Yifang Zhu; Weimiao Li; Yongan Zhou; et al. (Apoptosis, 2015)

ITS sequence-based identification and utilization evaluation of “Nanjiang” (Lonicera similis Hemsl.), a local cultivar in Sichuan, China - Shangqin Hu; Guiling Dong; Xiaomin Chen; Lulin Huang; Xiao Yang; Wen Tong; Linhan Bai (Genetic Resources and Crop Evolution, 2012)

Identification of Genes Involved in Immune Response, Microsatellite, and SNP Markers from Expressed Sequence Tags Generated from Hemocytes of Freshwater Pearl Mussel (Hyriopsis cumingii) - Zhiyi Bai; Yuxin Yin; Songnian Hu; Guiling Wang; Xiaowei Zhang; Jiale Li (Marine Biotechnology, 2009)